Current approaches to resilience programming among nongovernmental organizations - Frankenberger, Timothy R.; Constas, Mark A.; Nelson, Suzanne; Starr, Laurie (International Food Policy Research Institute, 2014)
This paper seeks to enhance our understanding of resilience processes, activities, and outcomes by examining initiatives to enhance resilience capacity that are designed and implemented by nongovernmental organizations (NGOs). The paper begins with a review of the evolution in thinking about the concept of resilience that has occurred over the past five years. This is followed by a review of the wide range of strategies and interventions employed by NGOs to build resilience capacity. The paper then presents several case studies that highlight NGO efforts to enhance resilience either by focusing on a specific vulnerable population and shock or by integrating, sequencing, and layering activities to support and protect core programming goals (for example, food and nutrition security, poverty reduction) while contributing overall to enhanced resilience capacity. Finally, the paper reviews measurement issues related to resilience, the challenges encountered by NGOs, and lessons learned. The paper concludes with a number of recommendations for improving NGO resilience programming.